2016
DOI: 10.1186/s13052-016-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum and CSF adiponectin, leptin, and interleukin 6 levels as adipocytokines in Egyptian children with febrile seizures: a cross-sectional study

Abstract: BackgroundA febrile seizure (FS) is the most common convulsive disorder in children. Activation of cytokine network is involved in FS pathogenesis. Adiponectin, leptin and IL-6 are the major adipocytokines secreted by fat cells. To date, only a few studies concerned the association of adipocytokines with febrile seizures. In this study, we tried to investigate serum and CSF levels of adiponectin, leptin, and interleukin-6 (IL-6); as adipocytokines, for the first time in Egyptian children with febrile seizures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 28 publications
6
33
0
Order By: Relevance
“…Analysis of the four adipokines showed that some of the results were similar to previous studies (8,(11)(12)(13), but this study also has new findings. A study by Turkish Güven et al (11) found that the levels of adiponectin and IL-6 in children under the age of 3 in the FS group were significantly higher than those in the HC group (p < 0.05), which is consistent with the results of the present study, but there was no statistical difference in serum adiponectin and IL-6 levels between the FS and FC groups in Güven's study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Analysis of the four adipokines showed that some of the results were similar to previous studies (8,(11)(12)(13), but this study also has new findings. A study by Turkish Güven et al (11) found that the levels of adiponectin and IL-6 in children under the age of 3 in the FS group were significantly higher than those in the HC group (p < 0.05), which is consistent with the results of the present study, but there was no statistical difference in serum adiponectin and IL-6 levels between the FS and FC groups in Güven's study.…”
Section: Discussionsupporting
confidence: 89%
“…In Güven's study, information about antipyretics is not provided. In addition, it should be noted that the age of previous studies (8,(11)(12)(13) is <3-years-old. In this study, the age range is large, and there is no difference in the number of children over 3 years old and children under 3 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IL-1β also stimulates IL-6 release ( 25 ). After a febrile seizure, children had significantly higher serum IL-6 levels than a healthy control group ( 26 ), and IL-6 levels had a descending trend during the time of recovery from the seizure in the intractable epilepsy group and the non-intractable epilepsy group ( 27 ), indicating that high IL-6 levels may be a pathogenetic factor in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…71 Previous clinical reports have associated elevated levels of IL-6 with the occurrence of febrile seizures. 72,73 IL-6 is a proinflammatory cytokine, which can play a role in neuroinflammation and seems to contribute to the impact of inflammatory signaling on seizure thresholds. A preclinical study reported an intensification of seizures in response to intranasal IL-6 administration in a seizure model in rats.…”
Section: Cov-2 and Seizuresmentioning
confidence: 99%